Subsurface profiling using horizontal drilling indices for guided boring method - Khondoker, Md. Tareq Hossain (2016)
Guided boring method (GBM) is a widely used trenchless technique to install pipelines with grade precision. As the length of these projects is much smaller than other underground projects (e.g. tunnels), conducting geotechnical investigations for GBM becomes unjustified at times due to budget constraints. Therefore, contractors will often conduct GBM installations without performing a proper subsurface investigation, which may lead to unusual consequences for the project. Since GBM consists of an initial pilot tube installation with further borehole reaming, the drilling parameters during the pilot tube installation phase may be used for subsurface profiling, which helps operators select proper drilling tools for the next reaming stages. This paper investigates the effectiveness of drilling parameters during pilot tube installation for subsurface profiling using drilling indices for a GBM project in Edmonton, Canada. Six drilling indices, which were proposed for vertical drilling, were used to obtain the comparative strength of soil throughout the drive length. The results indicated that all six indices could identify the soil transitions in the drive length. However, the indices can only give a comparative strength measurement of soil throughout the drive length, not the exact soil strength.